A Dandy Hand in Northeast Iceland An Examination of AM 640 4to, AM 621 4to, AM Dipl. Isl. Fasc. XVII 3, AM Dipl. Isl. Fasc. XXI 25, and JS Dipl. 4 - Kathrin Briana Gallagher 1992- (2019)
The intention of this thesis is to study two manuscripts, AM 640 4to and AM 621 4to, and three diplomas, JS Dipl. 4, AM Dipl. Isl. Fasc. XVII, 3, and AM Dipl. Isl. Fasc. XXI, 25 and attempt to answer two primary questions: 1.) Were these manuscripts and original documents written by the same scribe? 2.) Is there linguistic and orthographic uniformity across both manuscripts and diplomas? Scholars have previously posited that these manuscripts are most likely written in the same hand, but a presentation of why they believed this currently does not exist. This study will endeavor to provide evidence proving or disproving their claims by examining the paleographical, orthographical, and linguistic features of these five texts in a systematic manner. The data gathered by such an examination should reveal either a presence or lack of uniformity across the manuscripts and diplomas and will most likely offer more concrete evidence regarding the previous assertions on the scribal attribution of these texts. This thesis will begin with a brief yet thorough review of the manuscripts as they exist today. Following this will be an overview of the methodology which currently exists for determining scribal attribution, as well as a discussion on which methods will be applied in this thesis. A chapter on the examination of the script will follow, and it is this section which will be the driving force behind the study of scribal attribution. However, some information on the script will provide insights regarding the dates of the manuscripts and will be applied accordingly. Finally, an examination on the language and orthography of the manuscripts will conducted. The primary intention of this section will be focused on determining linguistic and orthographic uniformity across the manuscripts and diplomas to further assist with the study of scribal attribution. Markmið þessarar lokaritgerðar er að rannsaka tvö handrit, AM 640 4to og AM 621 4to, og þrjú fornbréf, JS Dipl. 4, AM Dipl. Isl. Fasc. XVII, 3, og AM Dipl. Isl. Fasc. ...